Structure of foreign language professionally-oriented speech competence (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2011)
The article deals with the structure of professionally-oriented foreign language speech competence comparing with the structure of general speech competence, taking into account specific character of their components.
Keywords: speech competence structure; basic component; professionally-oriented component; informationally-procedural component; organizationally-motivational component; criteria-effective component